FoodSharePro: An integrated mobile platform for sustainable food donation and decentralized composting - Jamil Alsayaydeh, Jamil Abedalrahim; Bacarra, Rex; Abd Gani, Shamsul Fakhar; Mamchenko, Serhij; Herawan, Safarudin Gazali (The Science And Information (SAI) Organization Limited, 2025)
Food waste is a global issue, one-third of all food produced is lost every year. This study introduces FoodSharePro, an integrated mobile-based Waste Food Management System that connects food donation and composting. The system allows for the efficient donation of surplus edible food through a mobile app and management of inedible waste through traditional composting methods. Built using Android Studio and Google Firebase, the app has secure authentication, location-based rider matching via Google Maps API and real-time data synchronization. Donors can log donations, track status and view delivery confirmations through a user-friendly dashboard, while riders are assigned tasks based on location and transport suitability. To minimize organic waste, composting hardware with temperature sensors and dehydration units supports aerobic composting process. Evaluation among 20 users showed that FoodSharePro has the highest satisfaction rate (75%) compared to 6 other platforms, with a mean user satisfaction of 24.29% and a standard deviation of 24.25%. The results prove that mobile technology can be integrated with grassroots waste management to reduce food loss and be sustainable.